A Novel Ferroptosis-Related Gene Prognosis Signature and Identifying Atorvastatin as a Potential Therapeutic Agent for Hepatocellular Carcinoma - Ling Wang; Xiaoqin He; Yang Shen; Jiayu Chen; Yukai Chen; Zhuolin Zhou; Ximing Xu (Current Issues in Molecular Biology)
Among the most common malignant tumors, hepatocellular carcinoma (HCC) is a primary liver cancer type that has a high mortality rate. HCC often presents insidiously, is prone to recurrence, and has limited treatment efficacy. Ferroptosis regulates tumorigenesis, progression, and metastasis, which is a novel form of iron-dependent cell death. Numerous studies suggest that HCC is sensitive to ferroptosis, indicating that targeted therapies aimed at inducing ferroptosis may represent a promising new approach to cancer treatment. This study aims to find genes associated with HCC and ferroptosis, as well as to screen for potential agents that may cause ferroptosis in HCC. Transcriptome and clinical sample data were obtained from the TCGA database to identify differentially expressed genes related to ferroptosis. Using various regression and survival analysis techniques, we developed a prognostic model based on four core genes and evaluated its predictive potential. Subsequently, we screened for potential therapeutic agents in the Connective Map (CMap) database, designated as compound Atorvastatin, based on differential genes from two risk groups and related to ferroptosis. Through experiments conducted in vivo and in vitro, we demonstrated that Atorvastatin can induce ferroptosis in HCC cells while inhibiting their growth and migration. In conclusion, this research targets ferroptosis therapy and provides new insights for improving the prediction and prevention of HCC.